KETAHANAN PANGAN DAN COPING STRATEGY RUMAH TANGGA DI PULAU TERISOLIR GILI LABAK, KABUPATEN SUMENEP, MADURA - Faradita Meilinda Wulan Sari; Annis Catur Adi (Media Gizi Indonesia, 2016)
Madura island is still facing challenges in development, including development related to food security. Food security has a strong linkage with poverty. Unavailability of food in sufﬁ cient quantity and quality is a major cause of  household food security problems. The objective of this study was to determine the level of  household food security and  coping strategy in  isolated island. This study was an observational research with descriptive and cross-sectional design, using a mixed method approach which combines qualitative and quantitative approach. The study was taken in Gili Labak island of Sumenep, M adura. The sample was all households live in Gili Labak island as much as 36 household. Household food security data was assessed using United States Household Food Security Modul (USHFSSM) instrument, while c oping strategy data was assessed using Reduced Coping Strategy Index (RCSI) instrument. The results of this study showed that most households were food insecure and make several efforts of  coping strategy for survival. The most common c oping strategy done by the household is borrowing food from neighbors. The study recommends there should be centers of seeds alternative crops other than rice as well as the intervention of the food aid before the arrival of the wave season, provision of water reservoir and food storage barns.